To evaluate the effects of antidepressant drugs on pregnancy outcomes in a university hospital in Turkey - Tugba Cavusoglu; Omer Can Atak; Erhan Eser; Ertan Dariverenli; Pelin Akca; Ercument Olmez (Journal of the Pakistan Medical Association, 2020)
Objective: To assess the effects of antidepressant use on pregnancy outcomes. Methods: The cross-sectional study was conducted at the Department of Pharmacology, Manisa Celal Bayar University, Manisa, Turkey, and comprised pregnant women who were admitted to the Department of Gynaecology between 2008 and 2017 who had been prescribed antidepressant drugs before pregnancy and continued to use them during any week of their respective pregnancies. The women were contacted by telephone after delivery to obtain information about the pregnancy outcomes. Data was analysed using SPSS 23. Results: There were 183 women with a mean age of 31.3 ± 5.3 years (range: 18-44 years). There were congenital defects in the newborn in 11(7.65%) cases. The most commonly used antidepressant group was selective serotonin reuptake inhibitor 138(75.4%), and escitalopram was the most frequently used drug 46(25.1%). Spontaneous abortion rate was higher with escitalopram than the other antidepressants (p=0.062). Induced abortion rate was significantly higher in multidrug users compared to those on a single drug (p<0.05). Conclusion: selective serotonin reuptake inhibitor was found to be the most used class of antidepressants during pregnancy due to the low side effects and teratogenic effects. When antidepressant treatment is necessary during pregnancy, a single drug can be more suitable. Key Words: Antidepressant, Pregnancy, Spontaneous abortion, Teratogenic effect.